MORPHOLOGICAL EVIDENCE FOR PROTANDRIC SIMULTANEOUS HERMAPHRODITISM IN THE CARIDEAN EXHIPPOLYSMATA OPLOPHOROIDES - Braga, Adriane A.; Lopez Greco, Laura S.; Santos, Daniela C. [UNESP]; Fransozo, Adilson [UNESP] (Crustacean Soc, 2009)
This study analyzed and described the sexual system of Exhippolysmata oplophoroides through the study of primary and secondary sexual characters at macroscopic and microscopic levels, to address the question of the existence of gonochorism or hermaphroditism in this species. The shrimps were collected in the Ubatuba region, São Paulo, Brazil. A total of 487 individuals were examined, sexed, and measured. They were dissected and their gonads were fixed, sectioned, and stained. All individuals had ovotestes, oviducts. ejaculatory ducts, appendices masculinae. and gonopores on the coxae of the fifth pereiopods. Female gonopores were found only in shrimp above 6.0 mm carapace length (CL). According to the characters studied. E. oplophoroides is a protandric simultaneous hermaphrodite with a male phase and a simultaneous hermaphrodite phase and these findings confirm some recent experimental evidence from mating pairs. The gonad of the male phase consisted of paired ovotestes with an undeveloped ovarian portion. In the hermaphroditic stage, most individual, had small appendices masculinae, both male and female gonopores. and ovotestes with vitellogenic oocytes and spermatozoa. The present study is the first detailed morphological description of the sexual system of Exhippolysmata oplophoroides. Our results are discussed in the light of new findings.
Keywords: Caridea; gonadal development; hermaphroditism; Hippolytidae; protandry